Impact of Forensic Accounting and Investigation on Corporate Governance in Ekiti State - OLAOYE, Clement Olatunji; OLANIPEKUN, Comfort Temidayo (Journal of Accounting, Business and Finance Research, 2018)
This study examined the impact of forensic accounting and investigation on corporate governance in Ekiti State. The primary data used were gathered through a well - structured questionnaire, designed and administered to 100 forensic accountants and the practitioners in Ekiti State. The returned questionnaires were coded and analysed using a binary logistic regression techniques and it was revealed that 76.2 percent of the time that forensic accounting and investigation enhanced corporate governance were correctly classified and in overall, it was 80.4 percent. Also, it was discovered that the probability value of the fraud detection and internal control system which were 0.997 and 0.997 ˃ 0.05 implies that fraud detection and internal control system contributed significantly to the corporate governance. Cox and Snell’s R-Square revealed that 51.7 percent of the variation in the corporate governance was explained by the logistic model. The Nagelkerke’s R2 indicated a moderate strong relationship of 69.1 percent between the forensic accounting and the corporate governance. Based on this finding, study concluded that forensic accounting and investigation would effectively impacted corporate governance by improving the management accountability, internal control system and financial reporting system.